2019
DOI: 10.1051/alr/2019011
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle of the blue jack mackerel,Trachurus picturatus(Bowdich, 1825), off the Portuguese continental coast

Abstract: This work provides for the first time a description of the reproductive biology of Trachurus picturatus in Portuguese continental waters (between 41° 49′ and 36° 57′ latitude North). From January 2010 to December 2016 a total of 7409 individuals were sampled from bottom trawlers operating on the northwestern coast of Portugal. The observed sex ratio was 0.56 in favor of the females. Monthly variations in gonadosomatic index, proportion of actively spawning individuals, hepatosomatic index and Fulton′s conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Conversely, the best predictions of ovarian development were seen for reproductively active versus inactive females, with OOB error of only 10.72%, implying that a combination of GSI, month, FL, and depth can accurately distinguish reproductive activity. Our model supports previous work, which has suggested that simply assigning an active or inactive classification to fish can aid managers in identifying spawning seasonality or even spawning location (e.g., Lowerre‐Barbieri et al 2015; Brown‐Peterson et al 2017; Costa 2019). Finally, month became less important than FL when predicting the spawning activity of reproductively active fish.…”
Section: Discussionsupporting
confidence: 88%
“…Conversely, the best predictions of ovarian development were seen for reproductively active versus inactive females, with OOB error of only 10.72%, implying that a combination of GSI, month, FL, and depth can accurately distinguish reproductive activity. Our model supports previous work, which has suggested that simply assigning an active or inactive classification to fish can aid managers in identifying spawning seasonality or even spawning location (e.g., Lowerre‐Barbieri et al 2015; Brown‐Peterson et al 2017; Costa 2019). Finally, month became less important than FL when predicting the spawning activity of reproductively active fish.…”
Section: Discussionsupporting
confidence: 88%
“…Fulton's condition factor (K), also known as the length-weight factor, is used to determine the physiological state of a fish, including its reproductive capacity and sexual maturity as well as the influence of the environment (degree of nutrition) on the species (Costa, 2019;González-Kother et al, 2020). The condition factor is determined by the ratio relating the weight and the length of the fish according to the following formula: K = (TW/TL 3 ) x 100…”
Section: The Condition Factor (K)mentioning
confidence: 99%
“…Fulton's condition factor (K) is used to estimate seasonal changes in fatness under the influence of external (environment) or internal (physiological) factors (Costa, 2019).…”
Section: Condition Factor Kmentioning
confidence: 99%
“…Landings in the mainland Portuguese coast, although highly variable, reached an average value of ca 2800 tonnes/yr in the last decade. Despite its growing economic importance, there is few information on the reproductive strategy of the blue jack mackerel, apart from data on size at maturity and spawning season in the Portuguese continental coast (Costa 2019), Azores (Garcia et al 2015) and Canary Islands (Jurado-Ruzafa & Santamaría 2013), and the type of fecundity for Madeira Island (Vasconcelos et al 2017).…”
Section: Introductionmentioning
confidence: 99%